Prenatal sugar consumption and late-life human capital and health: Analyses based on postwar rationing and polygenic indices - Gerard J. van den Berg; Stephanie von Hinke Kessler Scholder; R. Adele H. Wang (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
Maternal sugar consumption in utero may have a variety of effects on offspring. We exploit the abolishment of the rationing of sweet confectionery in the UK on April 24, 1949, and its subsequent reintroduction some months later, in an era of otherwise uninterrupted rationing of confectionery (1942-1953), sugar (1940-1953) and many other foods, and we consider effects on late-life cardiovascular disease, BMI, height, type-2 diabetes and the intake of sugar, fat and carbohydrates, as well as cognitive outcomes and birth weight. We use individual-level data from the UK Biobank for cohorts born between April 1947-May 1952. We also explore whether one's genetic "predisposition" to the outcome can moderate the effects of prenatal sugar exposure. We find t hat p renatal e xposure t o d erationing increases education and reduces BMI and sugar consumption at higher ages, in line with the "developmental origins" explanatory framework, and that the sugar effects are stronger for those who are genetically "predisposed" to sugar consumption.
Keywords: I12; I18; I15; D45; 330; Nutrition; food consumption; gene-environment interplay; education; developmental origins